Dextrin and polyurethane graft copolymers as drug carrier: Synthesis, characterization, drug release, biocompatibility and in-vitro toxicity - Shukla A.; Maity S.; Ray B.; Maiti P. (My University, 2025)
Chemical modification of dextrin with polyurethane as a graft has been synthesized for controlled drug release for longer time period by maintaining the hydrophobic–hydrophilic balance. Estimation of the degree of grafting is visualized from the integrated peak area in the NMR spectra. Particle nature of dextrin is converted into strip like morphology in polyurethane graft dextrin copolymers as obvious from atomic force microscopy. Drug release study of graft copolymers through in vitro studies indicates sustained drug release behavior as compared to pristine dextrin and specific interactions between polymer and drug have been verified through spectroscopic techniques. Biocompatibility of the graft copolymers has been revealed using cellular studies on cancerous HeLa cells through MTT assay and cell adhesion. Further, the cytotoxicity or the cell killing efficiency has been demonstrated resulting in significant cell mortality using the developed graft copolymers. © 2021